Arab Republic of Egypt : Staff Report for the 2006 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2006)
Economic conditions in Egypt are favorable, and the economic reform is moving forward. The discussions focused on the elements of a macroeconomic policy. IMF staff discussed the following with authorities: a multiyear fiscal consolidation plan, the monetary policy stance and strategy appropriate for maintaining inflation in low single digits, the exchange rate policy, and progress in financial sector reform. Executive Directors recommended the reforms that are needed to support central bank operational autonomy and strengthen policy formulation, and they also stressed the need to enhance the flexibility of labor and improve education.